2021
DOI: 10.3390/su13126625
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Face-to-Face, Emergency Remote Teaching and Smart Classroom: A Qualitative Exploratory Research Based on Students’ Experience during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic significantly disrupted traditional face-to-face teaching worldwide and forced education institutions to adopt new, online teaching formats to enable students to continue with their studies. This research focuses on students’ perceptions of three teaching different modalities: face-to-face (F2F), Emergency Remote Teaching (ERT) and Smart Classroom (SC), which were implemented in response to the restrictions enforced to combat the spread of COVID-19. A qualitative study based on two user e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 68 publications
4
61
0
3
Order By: Relevance
“…The main inputs of this design of each subject are the definition of content and methodologies along with the needs of academic staff and infrastructures. At this level should also be included the Smart Classroom (SC) [82,83], a technology that offers new teaching and learning possibilities and that was deployed in most of classrooms and laboratories in September 2020 at La Salle URL. Once classes begin, a review and update mechanism must be established.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main inputs of this design of each subject are the definition of content and methodologies along with the needs of academic staff and infrastructures. At this level should also be included the Smart Classroom (SC) [82,83], a technology that offers new teaching and learning possibilities and that was deployed in most of classrooms and laboratories in September 2020 at La Salle URL. Once classes begin, a review and update mechanism must be established.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in the case of implementing some students' opinions, engagement can increase since they perceive that their ideas have been valued and applied [41]. Another option that may enhance engagement is to promote the use of new technologies by students [95], and once again, asking students about how they perceive their experience using technology [82] may be crucial. Finally, promoting peer-to-peer interaction also may increase engagement [96].…”
Section: Practical Implications Of the Findingsmentioning
confidence: 99%
“…Regarding the students, they switched to remote learning which allowed them to maintain their educational training despite mobility restrictions. However, different challenges arose when attending classes off campus, such as distractions or less effective student-instructor and student-student interactions [9]. In addition, different research works have reported issues in other areas, such as their wellbeing [49], learning capabilities or engagement levels [50].…”
Section: Technologies Deployed At La Salle Url To Cope With the Covid-19mentioning
confidence: 99%
“…The pedagogical system of La Salle URL evolved from an ERT solution implemented at the beginning of the second semester of 2019-2020 academic year to a SC deployment before the start of the 2020-2021 academic year [9]. In other words, it implied moving from a tactical solution (ERT) to cope with the COVID-19 pandemic, to a strategical approach based on the SC format.…”
Section: Technologies Deployed At La Salle Url To Cope With the Covid-19mentioning
confidence: 99%
See 1 more Smart Citation